2013
DOI: 10.1038/eye.2012.279
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of atropine eye drops among children diagnosed with myopia in Taiwan from 2000 to 2007: a nationwide study

et al.

Abstract: Purpose This study was conducted to examine the atropine eye drop prescription trend for children diagnosed with myopia, and to determine the factors associated with the prescription of atropine eye drops. Design This was a population-based cross-sectional study. Methods This study was conducted using a national representative sample from the National Health Insurance (NHI) claims data. All school children between 4 and 18 years of age who had visited an ophthalmologist and were diagnosed with myopia between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 30 publications
(42 reference statements)
1
34
0
1
Order By: Relevance
“…12,[28][29][30][31] Since low-concentration atropine is much better tolerated than atropine 1%, it is becoming the standard treatment in Asia, with almost 50% of myopic Taiwanese children receiving atropine eyedrops of varying concentrations. 32 Since most studies have been performed on Asian populations with high rates of myopia and myopic progression, it is unknown whether these results can be replicated in other regions with more diverse populations. We studied the clinical effects of atropine 0.01%, the lowest concentration shown to have an effect on myopic progression, 12 on an ethnically diverse group of children with low to moderate initial myopia.…”
Section: Introductionmentioning
confidence: 91%
“…12,[28][29][30][31] Since low-concentration atropine is much better tolerated than atropine 1%, it is becoming the standard treatment in Asia, with almost 50% of myopic Taiwanese children receiving atropine eyedrops of varying concentrations. 32 Since most studies have been performed on Asian populations with high rates of myopia and myopic progression, it is unknown whether these results can be replicated in other regions with more diverse populations. We studied the clinical effects of atropine 0.01%, the lowest concentration shown to have an effect on myopic progression, 12 on an ethnically diverse group of children with low to moderate initial myopia.…”
Section: Introductionmentioning
confidence: 91%
“…The retina, choroid and sclera all contain muscarinic receptors and have been identified as possible sites of action . Despite this, atropine is increasingly used in clinical practice for myopia control owing to numerous studies that have repeatedly demonstrated significant myopia control effects with its application …”
Section: Pharmacological Strategies Of Myopia Controlmentioning
confidence: 99%
“…Numerous studies have disclosed that atropine is effective in slowing the progression of childhood myopia . Despite potentially annoying side effects, including photophobia and blurred near vision, there is an increasing trend of atropine eye drop prescription for myopic children in Taiwan . Increasing time spent outdoors and reducing peripheral hyperopia with optical devices also have been proven to protect against the development of myopia .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Despite potentially annoying side effects, including photophobia and blurred near vision, there is an increasing trend of atropine eye drop prescription for myopic children in Taiwan. 17 Increasing time spent outdoors and reducing peripheral hyperopia with optical devices also have been proven to protect against the development of myopia. 18,19 Although the optimal mode of myopia prevention has not yet been made clear, it is desirable to have myopic children and their parents adhere to these interventions until stabilization of refractive status by the late teen years.…”
Section: Introductionmentioning
confidence: 99%